Proton versus Rover: A Business History Approach - Sharif, Mohmad Yazam (Journal of Business Management and Accounting, 2016)
The objective of this paper is to present some comparative findings on Proton, a car manufacturer in Malaysia and Rover Group, a British automobile manufacturer. The paper used a ‘Business History’ methodology tracking the exploits of the two firms from 1980 to 2000. Two in-depth interviews were conducted with two key informants – Nadzmi Salleh, former CEO of Proton and John Towers, the former CEO of Rover Group. Apart from that, the study also utilized secondary documents from various sources such British Aerospace and Honda Swindon. Proton and Rover are sources of national pride for Malaysia and England respectively. Yet their financial performance over time were said to be poor. Some efforts by the respective governments and the management of the two firms to improve the performance in both firms were highlighted. In terms of the current status of both firms, Proton is still surviving but Rover has been defunct since 2005.
Keywords: Business history methodology; British Leyland; narrative analysis; Proton; Rover